Strategi Pembelajaran Guru dalam Meningkatkan Mutu Belajar Siswa di Madrasah Aliyah Negeri Karo - Inom Nasution; Yuni Syafriani; Suci Ramadhani; Anggun Sari Fadilla; Dawi Nurjannah; Yogi Andrian; Imam Amir Musthofa; Sandy Franata Tarigan (FONDATIA, 2022)
The teacher is an educator who is assigned to provide knowledge. In providing knowledge, an educator must use learning strategies so that teaching and learning activities become fun and not boring so as to improve the quality of student learning. The main purpose of the discussion is to find out how the method of teachers from Madrasah Aliyah Negeri (MAN) Karo in delivering the material. The research was conducted using qualitative methods by collecting detailed data through interviews. Teachers at Madrasah Aliyah Negeri (MAN) Karo have different learning strategies for each subject in delivering the material, such as using understanding strategies by providing understanding through powerpoint or conducting learning activities outside the classroom (outdoor) by observing the development of plants around. Learning strategies are an important key in improving the quality of student learning by raising students' enthusiasm and making the classroom atmosphere more pleasant. Another strategy carried out by Madrasah Aliyah Negeri (MAN) Karo in improving the quality of learning for its students is by applying the principle where an educator becomes a father, mother, friend, brother, sister, and closest relative so that students feel comfortable and are not afraid to express themselves his opinion.